An evaluation of the Petty Officer Training program of the Republic of Indonesia police using the Kirkpatrick model - Junus Simangunsong; Langgeng Purnomo (REID (Research and Evaluation in Education), 2021)
This study aims to evaluate the Petty Officer Training Program Noken to determine the program's success based on predetermined character values. The program evaluation uses Kirkpatrick's evaluation model with four levels: reaction, learning, behavior, and result. The data were obtained using a questionnaire, observations, interviews, and documentation and analyzed using quantitative and qualitative descriptive techniques. Before the questionnaire and observation sheets were used, their readability was tested to the Super Team for the National Identity formed by the Republic of Indonesia Police Headquarters and experts in psychology and educational evaluation. The results of the instrument readability test showed excellent results, with a score of 4.8 on a scale of 1-5. However, some revisions were needed, especially for the instruments for policymakers and management. The results of the evaluation of the two groups show that for the assessment at level 1: reaction, the participants' reaction to the organizing committee and resource persons is very high, and there is just a need to pay attention to the availability of facilities. At level 2: learning, the achievement of key competencies is very significant in its assessment. At level 3: behavior, there are behavioral changes including diligence in doing worship, discipline in attending classes, neat and clean clothes, working in groups, communicating well, and accuracy and speed in completing daily tasks. At level 4: result, the level of achievement of character values is very significant. The effect of conditioning and the teaching of materials contributes very significantly to applying national identity in everyday life.